Gender articulated: language and the socially constructed self - Hall, Kira; Bucholtz, Mary (Routledge, 1995)
Gender Articulated is a groundbreaking work of sociolinguistics that forges new connections between language-related fields and feminist theory. Refuting apolitical, essentialist perspectives on language and gender, the essays presented here examine a range of cultures, languages and settings. They explicitly connect feminist theory to language research. Some of the most distinguished scholars working in the field of language and gender today discuss such topics as Japanese women's appropriation of "men's language," the literary representation of lesbian discourse, the silencing of women on the Internet, cultural mediation and Spanish use at New Mexican weddings and the uses of silence in the Anita Hill-Clarence Thomas hearings.
Donné en lecture au cours LIN2685, Hall, Kira, Lip Service on the Fantasy Lines, pp321-342.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; maternité; premier cycle; queer; sciences humaines; sociolinguistique; thématiques; études de genres

The Oxford handbook of language and sexuality - Hall, Kira; Barrett, Rusty (Oxford University Press, 2018)
Disponible en ligne à https://academic.oup.com/edited-volume/42645?login=true Donné en lecture au cours LIN2685, King, Brian W. "Language and embodied sexuality", pp1-20.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; outils; ouvrages de références; premier cycle; queer; ressource en ligne; sciences humaines; sexualité; sociolinguistique; thématiques